THE CONCEPT OF GASSĀN HAMDŪN ON HIS KITAB TAFSĪR MIN NASAMĀT AL-QUR’ĀN KALIMĀT WA BAYĀN - Hadrawi Abdullah (Universitas Islam Negeri Alauddin Makassar, 2019)
The purpose of this study is to find out Gassan Hamdun's concept in the book of Interpretation of the Qur'an of the Qur'an Sentence, the interpretation techniques, the systematic writing and its characteristics, the advantages and disadvantages of the book. The results of this study show that Gassan Hamdun used the Ijmali method in interpreting the verses of the Qur'an which are interpretations based on bi al-ma'sur interpretive books as well as other major interpretive books, namely those of the interpretation books scholars and scholars acknowledge the depth of knowledge of the authors of such books, such as Tafsir Jalalain in interpreting the verse of the Qur'an, the Interpretation of Imam Nasafi in interpreting the Qur'anic verse, Al-Alusi's Interpretation in explaining the sentence in the Qur'an and sometimes also interpret the verses and take the appropriate hadiths and al-nuzul asbab a verse, take the interpretation of al-nuzul verses and asbab al-nuzul a verse in the Ibn Katsir interpretation, taking reference to the knowledge Shariah and its branches in the book